A participação do conselheiro independente nas companhias listadas no novo mercado da BM&FBovespa em 2012 - Gozzi, Paulo Roberto (2013)
The object of this paper is the corporate governance, specifically in relation to the role of the independent board members elected by the companies of Novo Mercado from BMF&Bovespa, by means of a qualitative study in order to verify the participation of the independent board members and the dynamics of decision process within such companies. The purpose of this work is to contribute to the corporate finance and corporate governance areas, specifically to explain several results of quantitative studies that deny a positive correlation between the proportion of independent board members and the financial performance of the companies. The survey was distributed by e-mail which was answered by 30 out of the total 361 independent board members and enabled the identification that the performance tasks of such members are directed by consulting activities and not by controlling activities, demonstrating that the dynamics within the boardroom in the decision process is in the direction of an alignment of interests and not of conflict. Furthermore, the study identified that reduced hours are dedicated in the actual performance of the functions of board members and, therefore, indicate that this may be one of the reasons to justify the lack of positive correlation between the proportion of board members and the financial performance of the companies. Therefore, the study suggests that, in the Brazilian environmental of high concentration of shares within reduced number of shareholders, the regulation authorities should be more active in their supervision functions, as the independent board member does not assume such role.